Investigation on Factors that Affect Students Speaking Skills: A Study on Grade 11 Studentss of St. John De La Salle Catholic School - Afeta, Lamessa; M, Rameh (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2025)
Most Ethiopian students cannot speak English fluently. The study's goal is to find out what factors have the greatest impact on students speaking skills in English. St. John Baptist De La Salle Catholic School's 2021/22 students were the participants of the study. The study employed a mixed approach. A random sampling method was used to select 70 students for this study. A questionnaire was used to collect primary data. Classroom observation was an additional resource that was utilized. To collect data on how students, communicate effectively in a foreign language and observe the methods that teachers used to teach speaking skills. As a result, most of the students had no desire to speak English both in and out of the classroom. In addition, the results showed that students' speaking abilities were negatively impacted by teachers teaching methods, lack of practice, large class sizes and lack of internet access. Language teachers must use interactive teaching methods, provide students with opportunities to communicate in English, and have students practice speaking in English as a way to overcome students' major difficulties in learning speaking skills.